Synthesis, characterization and activity evaluation of novel spiropyran-based ion sensors - Natali, Manuel (Trinity College (Dublin, Ireland). School of Chemistry, 2011)
Photochromism indicates a reversible transformation of a single chemical species induced in one or both directions by electromagnetic radiation between two states having different absorption spectra. Photochromic compound have been of great interest because of their unique properties. Indeed they have been employed in supramolecular assemblies such as polymers, liquid crystals, light-sensitive eyewear, information recording, optical memory, and molecular devices. Chemical modification of photochromic compounds has opened in the last decade new possibilities for developing systems that may be suitable for other purposes such as chemical sensing. This can be applied to countless analytes. In this research we focused on the synthesis of spiropyran based photochromic compounds designed for the selective and reversible detection of transition metal cations.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.